Introduction to CINEMA AND PSYCHOANALYSIS: THE WOMAN AS SHADOW OR MASK – Thematic Dossier - CÂMPEAN, Noemina (Studia Universitatis Babeș-Bolyai Philosophia, 2020)
Whereas Sigmund Freud regarded femininity as a mysterious, unexplored and even ʽdark continent, describing not what a woman is, but how does she come into being (the notorious question ʽWhat does a woman want?), Jacques Lacan argues that hysteria is an attribute of femininity (the question ʽWhat is a woman?) and proposes the concept of a feminine jouissance (Fr. la jouissance féminine, cf. Le Séminaire. Livre XX. Encore, 1972-73), which goes ʽbeyond the phallus but also regardless of the biological sex. In reference to the phallic signifier, the woman is exceptional because she exists on the side of the One. Moreover, she cannot be assigned a number, existing within the logic of the singular and of the infinite. Yet, the woman is bound to wear the phallic mask: she doesn’t possess the phallus, but she must behave like she has it.